The Influence of TikTok Social Media Commerce Promotional Content and Viral Marketing on Buying Interest in Corkcicle Products with the Lifestyle of Gen Y Teenagers and Gen Z As Moderating Variables - Niken Wukirsari; Albert Kriestian Adhi Nugraha (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyse the influence of TikTok social media commerce promotional content and viral marketing on Corkcicle product purchase interest among Gen Y and Gen Z teenagers. This study uses an online survey method with a sample of 100 respondents. The study results show that TikTok's social media commerce promotional content and viral marketing significantly affect Corkcicle's product purchase interest. The lifestyle of Gen Y and Gen Z teenagers acts as a moderating variable that strengthens this influence. This study contributes to digital marketing theory and provides strategic recommendations for business actors who use TikTok as a marketing channel.